Contributions of Muslim scholars attributed to other scholars in engineering and medicine - Banu, Asfana; Shuriye, Abdi Omar (Center for Promoting Ideas, 2017)
Muslim scholars during the Golden Age of Islamic history are known to have a great interest and respect in all kinds of knowledge especially knowledge related to applied science and technology; which can be useful in satisfying the needs of mankind. The developments of science and technology especially in engineering and medicine were actually available before the 14th century. However, historically, Muslim contributions towards science and technology have been neglected, ignored and to make it worse these contributions were attributed to other scholars and researchers